TEACHING THE TECHNIQUE OF BALL HANDLING IN BASKETBALL EFFECTIVENESS OF ENHANCING ACTIVITY (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The modern level of basketball development requires a lot of changes in the process of improving technical and tactical methods, which are closely related to the manifestation of special physical qualities and, in particular, to the level of their speed-power training.